Peningkatan dan Pelatihan Literasi Media Digital Anti Hoax, Bullying, dan Ujaran Kebencian di Rumah Tahfidz Quran Abulyatama - Dzikri Aprila; Rizky Mutaqien; Muhamad Rizal Nurul Hadi; Fathi Ridwan Alamsyah; Ade Iskandar Zulkarnaen (Jurnal Pengabdian Literasi Digital Indonesia, 2022)
The development of information and communication technology today has changed the way humans interact with each other. Social media is one of the media that allows humans to interact without being limited by space and time. The most dominant social media users are teenagers. With the rise of social media users for teenagers and even minors, it can certainly have a bad impact, if not used wisely. This is because most teenagers still have an unstable nature and cannot distinguish between real-world communication and the virtual world. The bad impact of using social media can be in the form of social problems such as cyberhate and cyber bullying . This service has the main goal of providing education to recipient partners about cyberhate and ethics in social media, targeting participants, especially teenagers and generally for the surrounding community. The target of its activity partners is the non-formal educational institution Rumah Tahfidz Quran Abulyatama which is located in Tarogong Kaler, Garut. The implementation method is carried out offline which takes place once a week within a month, by providing general and special services. General services are in the form of hate speech material, while special services are tailored to the needs of partners, namely material about blogspot. The results achieved are that participants can use social media properly and correctly and have ethics in social media.